PENGARUH PENGGUNAAN INFORMASI AKUNTANSI DAN MANAJEMEN MODAL KERJA PELAKU UMKM TERHADAP KEBERHASILAN USAHA DENGAN UMUR USAHASEBAGAI VARIABEL PEMODERASI (STUDI KASUS PADA INDUSTRI KREATIF DI YOGYAKARTA) - Khoirunnisa Cahya Firdarini; Agung Slamet Prasetyo (JURNAL STIE SEMARANG, 2020)
Small and medium enterprises (SMEs) are one of important sector of national economic that have contributed to labor absorption and Gross Domestic Product (GDP). They could survive of financial crisis both in national and global scale. This research examines the effect of accounting information and working capital management toward business success of small and medium enterprise (SMEs) with age of business as moderating variable. The population of this research are small and medium enterprises (SMEs) in creative industries sector operated in Yogyakarta district. They are handycraft, culinary and fashion. Based on purposive sampling method, total sample of this research is 200 SMEs. Hypothesis testing used is path analysis using structural equation modelling (SEM). The test result shows that accounting information and working capital management have positive and significant effect to the success of SMEs.Age of business as moderating variable also have positive and significant effect to the success of SMEs.